2007
DOI: 10.1073/pnas.0706233104
|View full text |Cite
|
Sign up to set email alerts
|

Structure, inhibitor, and regulatory mechanism of Lyp, a lymphoid-specific tyrosine phosphatase implicated in autoimmune diseases

Abstract: The lymphoid-specific tyrosine phosphatase (Lyp) has generated enormous interest because a single-nucleotide polymorphism in the gene (PTPN22) encoding Lyp produces a gain-of-function mutant phosphatase that is associated with several autoimmune diseases, including type I diabetes, rheumatoid arthritis, Graves disease, and systemic lupus erythematosus. Thus, Lyp represents a potential target for a broad spectrum of autoimmune disorders. Unfortunately, no Lyp inhibitor has been reported. In addition, little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
208
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(227 citation statements)
references
References 32 publications
12
208
1
4
Order By: Relevance
“…1). Previous studies showed that Lyp preferentially dephosphorylates Lck at Tyr(P) 397 in the activation loop over the autoinhibitory Tyr(P) 505 at its C terminus (11,22). Consistent with this finding, the k cat /K m value for the Lck Tyr 394 peptide (Ac-ENDEpYTARE-NH 2 ) is 10.3-fold higher than that of the Tyr 505 peptide (Ac-TEPQpYQPGE-NH 2 ) (Table 1).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…1). Previous studies showed that Lyp preferentially dephosphorylates Lck at Tyr(P) 397 in the activation loop over the autoinhibitory Tyr(P) 505 at its C terminus (11,22). Consistent with this finding, the k cat /K m value for the Lck Tyr 394 peptide (Ac-ENDEpYTARE-NH 2 ) is 10.3-fold higher than that of the Tyr 505 peptide (Ac-TEPQpYQPGE-NH 2 ) (Table 1).…”
supporting
confidence: 77%
“…Crystallization, Data Collection, and Structure Determination-The N-terminal His 6 -tagged catalytically inactive Lyp/C227S (residues 1-294) mutant was crystallized with the phosphopeptides under conditions similar to those reported previously (22). The co-crystals of Lyp/C227S with the consensus or the SKAP-HOM peptide appeared after 3 days and grew to 0.1 ϫ 0.2 ϫ 0.2 mm after 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu et al have demonstrated that the phosphatase function of LYP is regulated by phosphorylation at Ser-35. The phosphorylation at this residue alters the conformational state of LYP and impairs its phosphatase activity resulting in an augmentation of TCR signal transduction [13]. The role of LYP as a regulator of TCR signaling is also bolstered by the development of a salicylic acid-based LYP inhibitor which binds to the catalytic site and enhances TCR signaling [13].…”
Section: Known Function Of Lymphocyte Tyrosine Phosphatase (Lyp)mentioning
confidence: 99%